2017
DOI: 10.1088/1361-6463/50/10/103001
|View full text |Cite
|
Sign up to set email alerts
|

Improving, characterizing and predicting the lifetime of organic photovoltaics

Abstract: This review summarizes the recent progress in the stability and lifetime of organic photovoltaics (OPVs). In particular, recently proposed solutions to failure mechanisms in different layers of the device stack are discussed comprising both structural and chemical modifications. Upscaling is additionally discussed from the perspective of stability presenting the challenges associated with device packaging and edge protection. An important part of device stability studies is the characterization and the review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
43
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 214 publications
(200 reference statements)
0
43
0
1
Order By: Relevance
“…Various published reports demonstrated extrapolated operational lifetimes of OPV for several years 4,5,7,8,11 . A recently published review 3,6,9 revealed an increase in publication activities on OPV stability research and an increase in average reported lifetimes over the recent years, clearly demonstrating progress in the field. The observed experimental lifetimes range up to 2 years 8,10 , when no extrapolations to T80 (corresponding to efficiency drop to 80% of the initial efficiency value) or TS,80 (corresponding to efficiency drop to 80% after stabilization) were considered 11,12 .…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…Various published reports demonstrated extrapolated operational lifetimes of OPV for several years 4,5,7,8,11 . A recently published review 3,6,9 revealed an increase in publication activities on OPV stability research and an increase in average reported lifetimes over the recent years, clearly demonstrating progress in the field. The observed experimental lifetimes range up to 2 years 8,10 , when no extrapolations to T80 (corresponding to efficiency drop to 80% of the initial efficiency value) or TS,80 (corresponding to efficiency drop to 80% after stabilization) were considered 11,12 .…”
Section: Introductionmentioning
confidence: 98%
“…Power conversion efficiencies of 13-14% were obtained in single junction, bulk-heterojunction organic solar cells (BHJ OSC) 1,2 and operational lifetimes in the range of 10 years [3][4][5] were estimated on the basis of exclusively intrinsic degradation processes. Roll-to-roll processed flexible modules have already demonstrated outdoor stabilities of several years 6 . While this is very encouraging and promising, more understanding is required in terms of how materials properties impact the device stability.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[12]- [15] To date, the lifetime of organic solar cells, defined by Ts80, [16] reached 10,000 hours (417 days), [17] [18] and the main limitation is currently attributed to a low power conversion efficiency of the organic cell.…”
Section: Introductionmentioning
confidence: 99%